Application of technique of VES-stimulated phasal polarization for petroleum products pollution estimation of upper part of sedimentary cover (for example of "Usyn" area) - Вижва, С. А.; Нурмухамедов, В. Г.; Качан, І. А.; Рева, М. В.; Нікіташ, О. П.; Гончарук, А. П. (Київський національний університет імені Тараса Шевченка, 2005)
As a result of parametric investigation with VES-SPP (stimuled phasal polariration) carried out nearby river Uzyn was uncovered that kerosene pollution discreases resistability and increases the polariration of upper part of geological enviromental. So, as a leading method for petroleum products pollution investigations recommend the hindorless technique VES-stimulated phasal polariration with parametric drilling, seismic procpecting and gaz survey.

За результатами параметричних досліджень фазовим методом викликаної поляризації (ВЕЗ-ВПФ), виконаних поблизу р. Узин, встановлено, що забруднення гасом знижують опір і підвищують поляризовність верхньої частини вміщуючого геологічного середовища. При дослідженнях нафтопродуктових забруднень як провідний рекомендовано завадостійкий метод ВЕЗ-ВПФ в комплексі з інтерпретаційним бурінням, сейсморозвідкою і газовою зйомкою.
Використання методу ВЕЗ-ВПФ для оцінки забруднення нафтопродуктами верхньої частини осадочного чохла (на прикладі ділянки "Узин")
Keywords: оцінка забруднення; нафтопродукти; осадовий чохол; ділянка "Узин"; забруднення гасом; опір; поляризовність; інтерпретаційне буріння; сейсморозвідка; газова зйомка; pollution; petroleum products; upper part of sedimentary cover; Uzyn area; kerosene pollution; resistivity; polarization; parametric drilling; seismic prospecting; gas survey